Identity of Tradition Name in Hindu Marriage in Julah Village, Tejakula Sub-District. Buleleng Regency, Bali - Lestawi, Nengah; Bunga, Dewi (Opción, 2019)
Julah Village,Tejakula Sub-district, Buleleng Regency, Bali has a unique tradition that provides a traditional name for couples and wives who are new to the marriage. The traditional name is used in social and religious activi- ties in the village environment, while the national administration continues to use the name stated in the identity card. Through this study will be discus- sed about the process of tradinion naming in the marriage ceremony of Hindu society in Julah Village, and the meaning contained from the naming of Adat in the marriage ceremony of Hindu society in Julah Village, Tejaku- la Sub-District, Buleleng Regency. This research is a qualitative study with the approach of the Hindu law which refers to the customary rules system in Julah village. The traditional naming process in Julah village is conducted by looking at historical aspects of traditional naming. Types of traditional names have been provided and obtained by the lottery system. The tradition naming is made with the conditions and ordinances stipulated in the custo- mary law of the Julah Village. The meaning contained in the tradition naming of Julah village is to defend the local wisdom, socioreligius meaning, the meaning of strengthening indigenous identities, and the meaning of the social status of the order and the meaning of the develop- ment of symbolic capital.